2017
DOI: 10.1523/jneurosci.2110-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression-Dependent Effects of TREM2 Deficiency in a Mouse Model of Alzheimer's Disease

Abstract: Neuroinflammation is an important contributor to Alzheimer's disease (AD) pathogenesis, as underscored by the recent identification of immune-related genetic risk factors for AD, including coding variants in the gene TREM2 (triggering receptor expressed on myeloid cells 2). Understanding TREM2 function promises to provide important insights into how neuroinflammation contributes to AD pathology. However, studies so far have produced seemingly conflicting results, with reports that amyloid pathology can be both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 1 publication
11
120
2
Order By: Relevance
“…Reduced TREM2 gene dosage was found to enhance amyloid pathology in one of the studies [78], while it decreased amyloid pathology in another study [7]. Importantly, the latter group recently showed that TREM2 deficiency in APP/PS1 mice lead to reduced amyloid burden at an early disease stage, while it enhanced amyloid burden at a late disease stage [79]. When AD pathogenesis is investigated in transgenic mouse models, human ApoE isoforms are often expressed, either by using a heterologous promoter [80] or by gene replacement in animals devoid of murine ApoE [81].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced TREM2 gene dosage was found to enhance amyloid pathology in one of the studies [78], while it decreased amyloid pathology in another study [7]. Importantly, the latter group recently showed that TREM2 deficiency in APP/PS1 mice lead to reduced amyloid burden at an early disease stage, while it enhanced amyloid burden at a late disease stage [79]. When AD pathogenesis is investigated in transgenic mouse models, human ApoE isoforms are often expressed, either by using a heterologous promoter [80] or by gene replacement in animals devoid of murine ApoE [81].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been mixed results on the accumulation of Aβ, all Trem2 −/− studies have shown decreased clustering of myeloid or microglial cells around plaques, suggesting a defect in microgliosis, or microglia activation [30, 31, 42, 43, 45, 47]. These studies have also found that Trem2 −/− mice have fewer microglia and increased microglia apoptosis.…”
Section: Trem2 In Diseasementioning
confidence: 96%
“…Although there have been reports of TREM2 detection on non-myeloid/microglial cells in the CNS [4, 36], these cases have largely used immunostaining methods to identify neuronal expression of TREM2, which may identify sTREM2 produced by microglia that is released and bound to neurons which express a TREM2 ligand [26, 3739]. RNA expression analyses have confirmed Trem2 is expressed selectively on microglia in the brain [40, 41], and parabiosis experiments show these microglia are most likely resident microglia and not infiltrating monocytes [42], although this is still controversial [43]. Within human AD brain, laser microdissection showed Trem2 is highly expressed on plaque-associated microglia [44], and high resolution microscopy techniques showed that TREM2 protein is concentrated on microglia processes that are in contact with amyloid beta (Aβ) plaques [45].…”
Section: Trem2 In Diseasementioning
confidence: 99%
See 2 more Smart Citations